Labor supply and commodity demands - an application to Irish data - Murphy, A.; Thom, D. Rodney (Economic & Social Studies, 1987)
Annual Irish data are used lo estimate a model which allows for the joint determination of commodity demands and labour supply. Consumer preferences are modelled by a cost function of the Gorman polar form which permits exact linear aggregation over individuals with different money wage rates. Separability between goods and leisure is rejected by the data. Labour supply is found to be a positive function of the wage rate.
Keywords: Labour supply - Ireland; Employment - Ireland